Pengaruh Profitabilitas Dan Likuiditas Terhadap Agresivitas Pajak Pada Perusahaan Subsektor Perdagangan Besar Dan Perdagangan Eceran Yang Terdaftar Di Bursa Efek Indonesia Periode 2017 - 2020 - Christy; Fitri Handayani (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
This study aims to examine the effect of profitability and liquidity as independent variables on tax aggressiveness as the dependent variable. Tax aggressiveness in this study is measured by the Effective Tax Rate by comparing the income tax expense with pre-tax profit. Profitability is measured by the ratio of return on assets, liquidity is measured by the current ratio.This type of research is quantitative using secondary data sources in the form ofannual financial reports or annual reports through the Indonesia Stock Exchange (IDX). The population used in this study is large trading and retail trading companies listed on the Indonesia Stock Exchange (IDX) starting from 2017 – 2020. The sampling technique in this study used purposive sampling with the specified research criteria so as to obtain a sample of 22 companies with data obtained as many as 88 data. The analytical method used is a multiple linear regression test, classical assumption test, determination coefficient test, F test and T test using the Statictical Package For the Social Sciences (SPSS) application program version 25.The results of the analysis of this study stated that partially profitability had a negative and significant effect on tax aggressiveness and liquidity had no effect on tax aggressiveness. While simultaneous profitability and liquidity affect the aggressiveness of taxes.